What leads to brand hate? Antecedents and outcomes of brand hate - Samar, Rahi; Mehwish, Ishtiaq; Hafiz Fawad, Ali; Mazuri, Abd Ghani (2021)
The purpose of this study is to investigate the concepts of brand hate. It presents the antecedents and outcomes of brand hate. The study demonstrates five components namely corporate social responsibility (CSR), product/service failures (FAL), negative past experience (NPE), symbolic incongruity (SIC), and ideological incompatibility (IDC) to trigger brand hate, which leads to two behavioral outcomes namely brand avoidance (BAV) and negative word of mouth (NWM). The study shows that corporate social responsibility (CSR) is negatively related to brand hate. Four components Product/Service failures, Negative past experience, Symbolic incongruity, and Ideological incompatibility are positively related to brand hate. Brand hate is positively related to two outcome variables Brand avoidance and Negative word of mouth. Prior studies have focused either on antecedents or the outcomes of negative feelings but do not include a comprehensive model that addresses these issues. The population of this study comprises individual living in three large cities of Pakistan. The data will be collected using survey questionnaire based on convenience sampling approach. Smart PLS software will be used to data analyse.